Pelaksanaan Tanggung Jawab Sosial Perusahaan Sarulla Operation Ltd Dalam Menangani Keluhan Masyarakat Atas Aktivitas Perusahaan Terhadap Masyarakat Di Kecamatan Pahae Julu Kabupaten Tapanuli Utara - Mercy Yuliana Sitompul; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
This study discusses the implementation of Sarulla Operation Ltd's corporate social responsibilityin handling community complaints about the company's activities towards the community in Pahae JuluDistrict, North Tapanuli Regency. Corporate Social Responsibility (CSR) is a continuing commitment fromthe business world to act ethically and contribute to the economic development of the local community orthe local community. Based on Article 74 paragraph (1) of the Limited Liability Company Law, henceforthreferred to as the Company Law, each company is obliged to budget and run CSR programs for theenvironment and society. The community wants the existence of companies to contribute to the welfare ofsociety. The purpose of writing this thesis, namely; First, to find out how the implementation of SarullaOperation Ltd's corporate social responsibility towards the community in Pahae Julu Subdistrict, NorthTapanuli Regency, Secondly, to find out how the complaint handling mechanism was carried out by SarullaOperations Ltd to the community on the impact of company activities in Pahae Julu District, TapanuliRegency North.The type of legal research used by the author is a type of sociological legal research. Thisresearch was conducted at Sarulla Operation Ltd. Company Sociological legal research uses primary dataand secondary data, while the population and samples are parties related to the problems studied, namelythe company and the community. The technique of collecting data in this study was library research,interviews and questionnaires.From the results of this study the authors conclude that CSR carried out by the company has beenimplemented well but there are still a number of programs that have not been implemented optimally,programs implemented by the company consist of education, health, agriculture or livelihood development,infrastructure improvement, culture, art and religion. The complaints handling mechanism carried out bythe company is tracking complaints and handling mechanisms, receipts of complaints, joint surveys andinvestigations, categorization and handling of complaints, resolutions, informing complainants aboutresolution, execution, feedback complaints, closing complaints, sources and responsibilities.Keywords: Corporate Social Responsibility – Corporate - Society